Reconstruction of tectonic-burial evolution history of Sinian Dengying Formation in Sichuan Basin based on the constraints of in-situ laser ablation U-Pb date and clumped isotopic thermometer(Δ47) - Anping HU; Anjiang SHEN; Yana CHEN; Jianyong ZHANG; Feng LIANG; Yongsheng WANG (Shiyou shiyan dizhi, 2021)
Reliable evolution curve of tectonic-burial history is essential for the research of the source rock evolution, reservoir formation and hydrocarbon accumulation of target strata of basin. Previous publications reported the tectonic-burial evolution history curves established depending on regional geological setting, formation (denuded) thickness, and tectonic movements, which were uncertain due to the difference in such geological understandings. For the ancient marine carbonates in China, which have experienced multiple tectonic movement reformation, it is more difficult to reconstruct tectonic-burial evolution history. In this paper, based on the identification of carbonate cements and the establishment of diagenetic sequence, through coupling carbonate laser ablation U-Pb dating and clumped isotope (Δ47) thermometer, two understandings were proposed: (1) The tectonic-burial curves of the Sinian Dengying Formation in the Sichuan Basin were established under the constraints of absolute age and temperature, which avoided the problems of uncertainty of tectonic-burial history curves in previous studies; (2) The new tectonic-burial history curve provided critical reference for study on the source rock evolution, reservoir origin and hydrocarbon accumulation of the Sinian Dengying Formation of the Sichuan Basin, revealing three stages of hydrocarbon accumulation in the Dengying gas reservoir including Silurian, Permian and Yanshanian-Himalayan periods. The proposed method of reconstructing tectonic-burial evolution curve is not only suitable for the ancient marine carbonates which experienced multiple tectonic movement reformation, but is also promising for the study of source rock evolution, reservoir origin and hydrocarbon accumulation.